(Nation) building civic epistemologies around nuclear energy in India. (4th December 2020) - Haines, Monamie Bhadra
ABSTRACT: Anti-nuclear activism demonstrates the significant challenges of uniting India under a shared 'civic epistemology' – a modality of collective public reasoning that binds the state and polities together through institutionally mediated practices of vetting policy-relevant knowledge and expertise. This article argues that Indian nuclear politics is better understood through the lens of politico-epistemological upheaval instead of a shared civic epistemology, understood as a byproduct of hegemonic relations between the state and civil society. Civic epistemologies must account for the failures of the Indian bourgeoisie and state in achieving hegemony through nuclear nationalism, and contend with how coercive state power circumscribes consensual politics and is often directed towards subaltern groups ambivalently enrolled in India's nation-building project. The ongoing political debilitation and sometimes death of activists who are deemed anti-state or anti-development underscore the need to construct socially robust processes of producing more just and inclusive civic epistemologies.